2014
DOI: 10.1055/s-0034-1381953
|View full text |Cite
|
Sign up to set email alerts
|

Weaning from Mechanical Ventilation

Abstract: For many critically ill patients admitted to an intensive care unit, the insertion of an endotracheal tube and the initiation of mechanical ventilation (MV) can be lifesaving procedures. Subsequent patient care often requires intensivists to manage the complex interaction of multiple failing organ systems. The shift in the intensivists' focus toward the discontinuation of MV can thus occur late in the course of critical illness. The dangers of MV, however, make it imperative to wean patients at the earliest po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 102 publications
0
9
0
1
Order By: Relevance
“…On the one hand, the dangers of mechanical ventilation make it an imperative to wean patients at the earliest possible time. 17 On the other hand, premature weaning and extubation can trigger significant respiratory distress, which can cause setbacks in the patient’s clinical course, including reinstitution of ventilator support and hemodynamic instability. 17 These factors correspond with higher mortality and prolonged ICU length of stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the dangers of mechanical ventilation make it an imperative to wean patients at the earliest possible time. 17 On the other hand, premature weaning and extubation can trigger significant respiratory distress, which can cause setbacks in the patient’s clinical course, including reinstitution of ventilator support and hemodynamic instability. 17 These factors correspond with higher mortality and prolonged ICU length of stay.…”
Section: Discussionmentioning
confidence: 99%
“… 17 On the other hand, premature weaning and extubation can trigger significant respiratory distress, which can cause setbacks in the patient’s clinical course, including reinstitution of ventilator support and hemodynamic instability. 17 These factors correspond with higher mortality and prolonged ICU length of stay. 18 Therefore, following the current guidelines, 14 we avoided an aggressive approach for early extubation, as reflected by a slightly longer weaning period, when compared to the existing literature data.…”
Section: Discussionmentioning
confidence: 99%
“…A study from 2018 showed that SIMV is rarely used during ventilator weaning worldwide [9]. The comparison between SIMV and PSV during traditional ventilator weaning demonstrated inferior performance of the SIMV mode, which presents greater respiratory muscle work [25], as it provides inadequate rest to the respiratory muscles [7], higher incidence of asynchronies and prolonged hospitalization and MV [7,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, especially in prolonged MV [3], it is associated with severe complications [2,4]. Ventilator weaning should rest on a balance between daring and safety [5,6], avoiding premature extubation or late weaning [7]. Importantly, information on MV in emerging countries is rather limited [8], and Brazil has a high mortality rate associated with the use of MV, showing an association with advanced age, high disease severity scores, tracheostomy, prolonged MV and medical diagnoses [8].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormally rapid respiration (tachypnea) may arise due to several pathophysiological conditions, such as fever, arterial hypoxemia, metabolic acidosis, anxiety, atelectasis, and pain (42). An extremely large increase in the inspiratory rate may lead to more serious problems (30,37). In such situations, the tidal volume moderately decreases and the breathing frequency substantially increases with increases in minute ventilation (20,38).…”
Section: Introductionmentioning
confidence: 99%